Strategies for minimizing information asymmetries in construction projects: project managers’ perceptions - Ceric, Anita (Journal of Business Economics and Management, 2014)
Communication risk is of crucial importance in construction projects. The situation in which one of the project parties is better informed than another is known as information asymmetry. This problem is addressed by the principal-agent theory. According to this theory, information asymmetries cause three problems: adverse selection, moral hazard, and hold up. The focus here is on strategies for minimizing information asymmetries in the construction phase. A survey of project managers was conducted to establish an understanding of the relative importance of risk-minimization strategies established in the literature: bureaucratic control (contracts), information systems, incentives (bonuses), corporate culture, reputation, and trust. The multi-attribute utility theory was used to analyze the responses. According to the project managers who participated in the survey, trust is the most important strategy in the construction phase, followed by bureaucratic control (contracts) and information systems.